1987
DOI: 10.1093/nar/15.24.10331
|View full text |Cite
|
Sign up to set email alerts
|

A cyanogen bromide fragment of S4 that specifically rebinds 16S RNA

Abstract: Escherichia coli ribosomal protein S4 was subjected to cyanogen bromide cleavage and was found to generate a complete cleavage product capable of rebinding 16S rRNA. This fragment, consisting of residues 1-103, was found to bind with an apparent association constant of 11 microM-1. This fragment was used in place of S4 in an in vitro reconstitution experiment. Although the particles formed had a protein composition not significantly different from reconstituted 30S ribosomal subunits, their sedimentation behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The Bacillus and E. coli S4 proteins are approximately 50% identical, and conservation is especially high in the region of the protein shown for E. coli S4 to interact with 16S rRNA (4,5). The proteins are likely to play very similar roles in ribosomal structure and function; the region of 16S rRNA with which S4 interacts is highly conserved in eubacteria, and active ribosomal subunits could be assembled in heterologous reconstitution experiments mixing E. coli and B. stearothermophilus components (16,22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bacillus and E. coli S4 proteins are approximately 50% identical, and conservation is especially high in the region of the protein shown for E. coli S4 to interact with 16S rRNA (4,5). The proteins are likely to play very similar roles in ribosomal structure and function; the region of 16S rRNA with which S4 interacts is highly conserved in eubacteria, and active ribosomal subunits could be assembled in heterologous reconstitution experiments mixing E. coli and B. stearothermophilus components (16,22).…”
Section: Resultsmentioning
confidence: 99%
“…E. coli JM103 and DH5a were used for propagation of bacteriophage M13 and plasmids, respectively; strain RZ1032 was used for preparation of uracil-containing M13 template DNA for oligonucleotide mutagenesis. Antibiotics were used at the following concentrations: ampicillin, 50 ,ug/ml; chloramphenicol, 5 ,ug/ml; neomycin, 5 p.g/ml; erythromycin, 1 ,ug/ml; and lincomycin, 25 ,ug/ml. Chloramphenicol and erythromycin were used at 0.1 ,ug/ml for induction of the cat and erm genes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The rpsDl and rpsD2 mutations result in the duplication or deletion of four amino acids within a region of the protein showing high conservation with the E. coli S4 protein (12). This region of the protein has been shown to be essential for binding of protein S4 to 16S rRNA in Escherichia coli (6,7). It was therefore of interest to examine the effect of the rpsD mutations on the growth properties of the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Not only was S4:Δ41 unable to bind the 5WJ in vitro (Fig. 1B), previous reconstitution experiments (Changchien and Craven 1976;Conrad and Craven 1987) showed that complexes containing S4:Δ41 lack a subset of secondary and tertiary binding proteins and were therefore nonfunctional. Thus the intrinsically disordered N-terminal extension of bacterial S4 contributes essential contacts for RNA recognition and viability.…”
Section: The δ41 Mutation Is Lethalmentioning
confidence: 76%
“…Early studies demonstrated that an S4 fragment missing the N-terminal flexible extension (S4:Δ41) (Fig. 1A, red) bound 16S rRNA with low micromolar affinity Craven 1976, 1978;Conrad and Craven 1987) and does not significantly rearrange its structure upon binding (Newberry et al 1977). Ribosome reconstitution experiments by Changchien and Craven (1976) and, later, Conrad and Craven (1987) showed that the S4 fragment could incorporate into ribosomal particles, although these particles were missing a subset of secondary and tertiary binding proteins.…”
Section: Resultsmentioning
confidence: 99%